A Pain in the Buttock - Zachary C. Landman; Shannon Beres; Michael D. Cabana (Case Reports in Pediatrics)
Spondylolysis, a fracture of the pars interarticularis, is a common source back pain in children and adolescents. While the incidence is significantly higher in Asian and Inuit populations, it is never seen in nonambulatory children and is most commonly associated with athletic activities that involve extension or rotational deformity about the spine suggesting a functional component. Given that the associated pain is typically insidious in onset, lacks preceding trauma, and is accompanied by muscular spasm, prompt diagnosis requires a high index of suspicion, familiarity with provocative testing, and knowledge of the appropriate radiographic evaluation. Treatment requires cessation of athletic activity, bracing, and rest for a minimum of four to six weeks, or until symptomatic and radiographic resolution.